2006
DOI: 10.1002/rcm.2768
|View full text |Cite
|
Sign up to set email alerts
|

Effective quenching of fragment formation in negative ion oligonucleotide matrix‐assisted laser desorption/ionization mass spectrometry through sodium adduct formation

Abstract: Metastable decay of the sodium-free and the sodium adducts of the negatively charged hexameric nucleotides 5'-d(TTXYTT)-3' (X and Y are dC, dG or dA) in matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-ToF-MS) is reported. We show that the sodium adduct formation may be used to quantitatively quench dissociation channels in oligonucleotide MALDI-MS, and we argue, that by means of effective steps in the sample preparation that lead to per-sodiation of the sample, the sample pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
16
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…Figure 1 shows PSD spectra of protonated 5=-d(TTCGTT) ions containing 0 -7 sodium ions. Similar to the deprotonated hexameric oligonucleotides, which we reported in an earlier study [12], the predominating channels observed for the protonated hexameric oligonucleotides are backbone cleavage through the w 3 and the a 4 -B 4 H fragmentation channels as well as single base loss. To a lesser extent we observe backbone cleavage through the w 2 channel.…”
Section: Methodssupporting
confidence: 76%
See 2 more Smart Citations
“…Figure 1 shows PSD spectra of protonated 5=-d(TTCGTT) ions containing 0 -7 sodium ions. Similar to the deprotonated hexameric oligonucleotides, which we reported in an earlier study [12], the predominating channels observed for the protonated hexameric oligonucleotides are backbone cleavage through the w 3 and the a 4 -B 4 H fragmentation channels as well as single base loss. To a lesser extent we observe backbone cleavage through the w 2 channel.…”
Section: Methodssupporting
confidence: 76%
“…The bulk of this work is reviewed by Wan and Gross in 2001 [13] and by Wu and McLuckey in 2004 [6]. Several different mechanisms have been suggested for the decay of negatively charged oligonucleotides studied, and the experimental data does not appear to support one single mechanism [9,10,[12][13][14][15]. For the protonated oligonucleotides, on the other hand, the bulk of the studies conducted show that the fragmentation (with the exception of the loss of terminal nucleotides or nucleosides and the loss of water) is initiated by the protonation of a high proton affinity base [6, 11, 14, 24 -26].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The instrument and its operation in PSD mode has been described in fair detail elsewhere [29] and here we only give a short overview. The MALDI-ToF is equipped with an N 2 laser (337 nm, 200 J/pulse) operated with 7-10 Hz repetition rate.…”
Section: Methodsmentioning
confidence: 99%
“…MALDI-TOF experiments have been performed in the Reykjavik laboratory with a REFLEX IV (Bruker Daltonics) instrument that is equipped with a time-of-flight (TOF) Reflectron type mass spectrometer and a pulsed N 2 laser (337 nm, 10 Hz, 400 μJ/pulse) [23]. Ion extraction is pulsed with 400 ns delay time.…”
Section: Methodsmentioning
confidence: 99%